Protocolized Sedation vs Usual Care in Pediatric Patients Mechanically Ventilated for Acute Respiratory Failure: A Randomized Clinical Trial. Issue 4 (August 2016) - Curley, Martha A. Q.; Wypij, David; Watson, R. Scott; Grant, Mary Jo C.; Asaro, Lisa A.; Cheifetz, Ira M.; Dodson, Brenda L.; Franck, Linda S.; Gedeit, Rainer G.; Angus, Derek C.; Matthay, Michael A.
Abstract : (Abstract from JAMA, 313:379–389, 2015) Few data inform sedation practices in pediatric critical care patients, despite notable variation and potential negative outcomes. In some cases, certain sedation therapies, specifically opioids and benzodiazepines, may impair bedside neurological assessment, depress spontaneous ventilation, and prolong mechanical ventilation.